Combined Thoracic Ultrasound Assessment during a Successful Weaning Trial Predicts Postextubation Distress. (October 2017) - Silva, Stein; Ait Aissa, Dalinda; Cocquet, Pierre; Hoarau, Lucille; Ruiz, Jean; Ferre, Fabrice; Rousset, David; Mora, Michel; Mari, Arnaud; Fourcade, Olivier; Riu, Béatrice; Jaber, Samir; et al.
Abstract : Background: Recent studies suggest that isolated sonographic assessment of the respiratory, cardiac, or neuromuscular functions in mechanically ventilated patients may assist in identifying patients at risk of postextubation distress. The aim of the present study was to prospectively investigate the value of an integrated thoracic ultrasound evaluation, encompassing bedside respiratory, cardiac, and diaphragm sonographic data in predicting postextubation distress. Methods: Longitudinal ultrasound data from 136 patients who were extubated after passing a trial of pressure support ventilation were measured immediately after the start and at the end of this trial. In case of postextubation distress (31 of 136 patients), an additional combined ultrasound assessment was performed while the patient was still in acute respiratory failure. We applied machine-learning methods to improve the accuracy of the related predictive assessments. Results: Overall, integrated thoracic ultrasound models accurately predict postextubation distress when applied to thoracic ultrasound data immediately recorded before the start and at the end of the trial of pressure support ventilation (learning sample area under the curve: start, 0.921; end, 0.951; test sample area under the curve: start, 0.972; end, 0.920). Among integrated thoracic ultrasound data, the recognition of lung interstitial edema and the increased telediastolic left ventricular pressure were the most relevant predictive factors. In addition, the use of thoracic ultrasound appeared to be highly accurate in identifying the causes of postextubation distress. Conclusions: The decision to attempt extubation could be significantly assisted by an integrative, dynamic, and fully bedside ultrasonographic assessment of cardiac, lung, and diaphragm functions. Abstract : Ultrasound examination was repeated before and after a pressure support trial (136 patients) and integrated models (lung, heart, and diaphragm) accurately predicted postextubation distress (area under the curve greater than 0.90); interstitial edema and elevated left ventricular diastolic pressure were most predictive. Integrated sonography might be valuable in assessing extubation readiness in the intensive care unit.Supplemental Digital Content is available in the text.